2019
DOI: 10.1002/jsfa.9622
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic analysis of the modulatory effect of Cyclocarya paliurus flavonoids on the intestinal microbiome in a high‐fat diet‐induced obesity mouse model

Abstract: BACKGROUND As a result of a low bioavailability, the majority of Cyclocarya paliurus flavonoids (CPF) remain in the large intestine where they accumulate to exert a modulatory effect on the intestinal micro‐ecology. Therefore, the present study investigated the modulatory effect of CPF on intestinal microbiota. RESULTS CPF dramatically ameliorated the obesity‐induced gut dysbiosis. A significant decrease (P < 0.05) was observed in the ratio of Firmicutes/Bacteroidetes after CPF treatment for 8 weeks. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 40 publications
(87 reference statements)
2
36
0
Order By: Relevance
“…Gut microbes can influence obesity by regulating metabolism, homoeostasis, appetite and energy balance, which together play crucial roles in obesity [ 25 ]. The structure, function and diversity of the gut microbiota among people with obesity are different from those of normal people [ 26 ]. Individuals with obesity usually show lower biodiversity and richness [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes can influence obesity by regulating metabolism, homoeostasis, appetite and energy balance, which together play crucial roles in obesity [ 25 ]. The structure, function and diversity of the gut microbiota among people with obesity are different from those of normal people [ 26 ]. Individuals with obesity usually show lower biodiversity and richness [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidetes species produce succinic acid, acetic acid, and in some cases propionic acid and plays an important role in protein metabolism. There is abundant evidence confirm that higher of Firmicutes/Bacteroidetes ratio of gut microbiota was found in obese patients ( De Bandt et al, 2011 ; Balfego et al, 2016 ; Louis et al, 2016 ) and HFD fed animals ( Huazano-Garcia et al, 2017 ; Wang H. et al, 2018 ; Cheng et al, 2019 ). Altered Firmicutes/Bacteroidetes ratio of gut microbiota in animals promotes increased ghrelin secretion correlated with MetS ( Perry et al, 2016 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, Cheng's FIGURE 10 | Funnel plot for publication bias in the meta-analysis. study showed that CP flavonoids can modulate gut microbiota to regulate certain metabolic processes, to the benefit of murine obesity models (60).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, publication bias and selective reporting may also have affected the cumulative evidence. Flavonoids and triterpenoids are more likely to be the effective compounds in CPEE, and further studies performed on these phytochemicals have shown positive results (13,18,(59)(60)(61). Meanwhile, as the main components found in CPAE, polysaccharides have been previously investigated.…”
Section: Discussionmentioning
confidence: 99%